A rare care of post covid thromboembolic disease involving both arterial and venous system - Aggrawal, Manav; Aggarwal, Mrigakshi; Aggrawal, Prem (Indian Journal of Case Reports, 2022)
The severe acute respiratory syndrome coronavirus disease (COVID-19) pandemic is caused by the novel severe acute respiratory syndrome coronavirus 2 and is affecting all civilizations. At present, there is an availability of minimum data highlighting the occurrence of thromboembolism in patients infected with COVID-19. Here, we report a rare case involving a 49-year-old female patient with thrombotic occlusion of the infrapopliteal artery and venous systems associated with COVID-19.